Pelatihan Strategi Pemasaran Produk Bagi Umkm Binaan Pusat Inkubator Bisnis Universitas Ottow Geissler Papua di Jayapura - Hilda Christine Flora Nahusona (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This community service is carried out for MSMEs in Jayapura City which are Tenants of the Business Incubator Center for the Ottow Geissler University Papua. The purpose of this community service is to hold training on Marketing Strategy for MSMEs as an effort to increase MSME understanding and skills in increasing sales of their products. The methods used in this community service are lectures, questions and answers, discussions and exercises. The results of this community service activity are expected that MSMEs can plan and conduct simple market research to find out customers and competitors so that they can increase product sales. The results of the PKM show that there are SMEs that are considered unable to deal with environmental changes optimally, which is characterized by not innovating, and not being able to compete with competitors, then these SMEs are still carrying out conventional marketing and there are also those that are considered to be able to deal with environmental changes optimally. which is marked by innovating in developing its products so that it is able to compete with competitors and has carried out modern marketing using social media.